A Study of Quantum dots of GaSb - M. Barmawi; Sugianto Sugianto; R.A. Sani; Euis Sustini; P. Arifin; M. Budiman (Institute for Research and Community Services (LPPM) ITB, 2001)
Abstract. Quantum Dots is a nano structured materials, which is an interesting object for fundamental study as well as for applications. Quantum Dots has been used for optoelectronic devices, such as fast detectors and for lasers. In this paper we report preliminary results of the preparation of quantum dots of GaSb in our laboratory. These dots are prepared by self-organized growth by MOCVD, using Trymethylgalium and Tridismethylaminoantimonat as metal organic sources and using GaAs as substrate. The results are studied by Scanning Electron Microscope. We propose further characterization of these quantum dots. Studi Mengenai Titik Kuantum GaSbSari. Quantum Dot adalah material yang mempunyai struktur nano, yang merupakan objek untuk penelitian fundamental maupun untuk penerapannya. Dalam makalah ini dilaporakan hasil-hasil yang pertama yang kita peroleh dalam pembuatan Quantum Dot dari GaSb dalam laboratorium kami. Quantum Dot ini telah ditumbuhkan dengan menggunakan penumbuhan yang